The Bulgarians of Bessarabia in the 1940s: factors of the demographic process, birth rate and mortality - Ganchev, Oleksandr (The Journal of Ethnology and Culturology, 2026)
The article examines the mechanisms of transformation in the demographic development of the Bulgarian population of Bessarabia in the 1940s under the influence of repression, forced displacement, and the famine of 1946–1947. It analyses the interaction between endogenous demographic factors of population reproduction and external circumstances related to socio-economic transformations during the 1940s. Birth rate as a historicaldemographic process is explored through four main analytical dimensions: the crude birth rate, variability of fertility indicators, age at first birth, and seasonality of births. Mortality represents a key indicator of the overall condition of society and its developmental processes. Together with the birth rate, mortality plays a fundamental role in shaping natural population change. This conceptual approach provides a solid basis for both retrospective and prospective studies of mortality. The study concludes that the transformation of fertility and mortality factors delineates two stages of the demographic transition. The first stage began in the last quarter of the nineteenth century, when high mortality declined as part of a broader process that included falling fertility rates. The second stage was driven by the intervention of the exogenous famine factor of 1946–1947 in the mechanisms of natural mortality, leading to a substantial transformation of its structure.